Dynamic Brain - from Neural Spikes to Behaviors - Marinaro, Maria (Springer, 2017)
This book is devoted to graduate students and researchers with different scientific background (including physics, mathematics, biology, neuroscience, etc.) who wish to learn brain science beyond the boundary of their fields.